Rational Emotive Behavior Therapy Counseling to Minimize Anxiety: Reviewed from a Theoretical Perspective - Larasati, Sectio Putri; Firman, Firman; Netrawati, Netrawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Anxiety is something that everyone tends to experience. Basically, individuals who are in an anxious state will find it difficult to think optimally and cannot carry out their activities smoothly and optimally like normal people in general. So that this anxiety is very important to be overcome and minimized so as not to have a negative impact on the life of the individual. The purpose of this study is to see theoretically that REBT counseling can minimize anxiety. The research uses a literature study method. The data in this study was obtained from various references such as books, articles, journals and other scientific studies that are related to REBT and anxiety counseling. The data in this study were analyzed, classified, processed, and described in an easy-to-understand and understandable language. Based on the results of the theoretical review, it can be understood that anxiety is a psychological problem that stems from the inability to think rationally. So it is suitable to be overcome by providing REBT counseling that focuses on rationalizing individual irrational thoughts, and can be used to reduce or minimize anxiety experienced by individuals. However, it must be done by a professional counselor who can implement this REBT counseling properly according to the stages that have been set.